2009
DOI: 10.1063/1.3089232
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of native point defects in crystalline indium gallium zinc oxide

Abstract: Articles you may be interested inA thermalization energy analysis of the threshold voltage shift in amorphous indium gallium zinc oxide thin film transistors under simultaneous negative gate bias and illumination Materials in In-Ga-Zn-O system are promising candidates for channel layers of high-performance thin-film transistors ͑TFTs͒. We investigated the atomic arrangements and the electronic structures of crystalline InGaZnO 4 containing point defects such as oxygen vacancy ͑V O ͒, interstitial hydrogen ͑H i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 37 publications
7
56
0
Order By: Relevance
“…The oxygen vacancy formation in InGaZnO 4 and the defect state location with respect to the conduction band edge of the oxide have been determined earlier [23,52]. In this work, we investigate how the presence of light-metal cations (Ca and/or Al) affects the distribution of the oxygen vacancies within the structurally and chemically distinct layers of multicomponent oxides.…”
Section: B Distribution Of Oxygen Vacancies In Inam O4mentioning
confidence: 99%
“…The oxygen vacancy formation in InGaZnO 4 and the defect state location with respect to the conduction band edge of the oxide have been determined earlier [23,52]. In this work, we investigate how the presence of light-metal cations (Ca and/or Al) affects the distribution of the oxygen vacancies within the structurally and chemically distinct layers of multicomponent oxides.…”
Section: B Distribution Of Oxygen Vacancies In Inam O4mentioning
confidence: 99%
“…Electronic band structure investigations of undoped stoichiometric InGaZnO 4 have been performed earlier for the crystalline [29,30] and amorphous oxide [63]. Most importantly, it was found that despite the different band gap values of the constituent single-cation oxides, cf., Table I, all cations give comparable contributions to the conduction band bottom of the complex oxide.…”
Section: Iv1 Undoped Stoichiometric Ingazno4mentioning
confidence: 99%
“…Also, it was assumed that each vacancy donates two extra electrons, i.e., there is no charge compensation via natural defects or defect complexes. However, it was shown theoretically [30] that uncompensated oxygen vacancy in InGaZnO 4 results in a deep level within the band gap and, thus, free carriers cannot be efficiently generated. Therefore, oxygen vacancy cannot explain the observed conducting behavior in this material.…”
Section: Introductionmentioning
confidence: 99%
“…1. The negative shift of the characteristics means the increase of shallow donor defects generating carrier electrons in the channel region, which is thought to be caused by the heat treatment at 400°C for 1 h. Although the origin of the shallow donor defects is still controversial, [28][29][30][31][32] we believe that it strongly correlates with oxygen vacancies in the CAAC-IGZO active layer. Instead of the origin of the shallow donor defects, we discuss, in the subsequent section, the influence of the donor concentration in the channel region on the I d -V g characteristics of an IGZO transistor, including an extreme case of the intrinsic channel.…”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30][31][32] As a result, it is believed that an IGZO transistor is also an n-type channel device in which electrons serving as majority carriers are controlled by a gate voltage. Actually, the transistor tends to be normally-on and it is hard to shift the threshold voltage in the positive direction.…”
Section: Introductionmentioning
confidence: 99%